Gowns in Towns. University Extensions in Transylvania (1919-1945) - Stan, Ana-Maria (CIAN-Revista de Historia de las Universidades, 2023)
This article provides a detailed, chronological and comparative analysis of the various forms of university extensions (adult education programmes) which functioned in Transylvania between 1919 and 1945. It highlights the contribution of the Cluj university professors to the regional socio-cultural life, as well as the importance of popularizing science to the general public. Knowledge dissemination through the so-called ‘popular lectures and courses’ was regarded as a valuable and important tool for modernizing the local society in the aftermath of the First World War and the reorganization of Transylvania as a province of the Romanian state (România Mare – Great Romania).